(untitled) (Journal of Philosophy Culture and Political Science, 2018)
On strengthening inter-confessional harmony and dialogue of leaders among world and traditional religions, Republic of Kazakhstan as international legal subject, demonstrates the example of respectful and neighborly co-existence of different confessions and ethnos to the whole world. The article focuses on convention of leaders of world and traditional religions which is passed in Astana, the essence of which is the strengthening of inter-confessional dialogue as one of major instruments of maintenance of the world and consent between people and nations, supports of effort of international association on advancement of dialogue between civilizations. Also in the article describes the policy of the state in these questions and the role of Orthodox Church in strengthening religious tolerance. Key words: Religion, state, politics, inter-confessional harmony, Russian Orthodox Church.